Fungicidal evaluation against green gram fungal pathogens - K.B. YADAHALLI*, M.C. KAVYASHREE and (Indian Phytopathology, 2016)
The fungicides hexaconazole 5% EC (0.1% and 0.15%), carbendazim 25% + mancozeb 50% WS (0.05%, 0.1% and 0.2%)and mancozeb 75 WP (at 0.1%, 0.2% and 0.25%) showed 100% inhibition of mycelial growth ofCercospora canescens over control. The fungicides tested againstColletotrichum gloeosporioides at three concentrations revealed that maximum per cent mycelial inhibition (100%) was recorded in treatments containing propiconazole 25% EC, trifloxystrobin 25% + tebuconazole 50% w/w (at 0.05%, 0.1% and 0.15%) and copper oxychloride 50 WP (at 0.25%). Copper oxychloride showed submerged growth under poisoned food technique. The slide germination bioassay of fungicides against Erysiphe polygoni revealed that maximum per cent inhibition of conidial germination was recorded in treatments containing hexaconazole 5% EC and azoxystrobin 250% SC at 0.15 per cent (100%).